If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1x+3=59
We move all terms to the left:
-1x+3-(59)=0
We add all the numbers together, and all the variables
-1x-56=0
We move all terms containing x to the left, all other terms to the right
-x=56
x=56/-1
x=-56
| -1x+3=39 | | x^2=+103x+17 | | 4x+16=10x+4 | | 11=0+b | | -8=x/6-6 | | 2^2+m2+3-m=0 | | x^2+2x+3-2=0 | | (x^2+4x)^2-17(x^2+4x)+60=0 | | 6n−5n=8 | | 90+x=25 | | 12(−4x+10)−3(2x−4)=−4+3(4x+2) | | 5^4x-6=25^6-x | | 800+30x=80x | | x^2=0.95x | | 2/5n-118=13.2 | | 3^x2-42=3^-x | | x+4•x-2=5•15 | | y=6,34+7 | | (x+8)2=−25 | | 25+s=120 | | x+4(x-2)=5(15) | | x+4(x-2)=20 | | 3(5+7x)=204 | | -3=10+n/2 | | 7x-(3x+5)-8=1/2(8×+20)-7×+5 | | 5/6+3j=2/3- | | a(44-4)=64 | | x/x+4.6=9.3 | | 64(44-4)=a | | 2x+90=x+95=180 | | 7(x+2)=30+x | | 3p-4+4=17/3 |